Persistent systemic monocyte and neutrophil activation in neonatal encephalopathy. (17th January 2016) - O'Hare, Fiona M.; Watson, R. W. G.; O'Neill, Amanda; Blanco, Alfonso; Donoghue, Veronica; Molloy, Eleanor J.
Abstract: Aim : Circulating immune cell activation is associated with worse outcome in adult and animal models of brain injury. Our aim was to profile the systemic inflammatory response over the first week of life in infants at risk of neonatal encephalopathy (NE) and correlate early neutrophil and monocyte endotoxin and activation responses with outcome. Methods : Prospective observational study in a tertiary referral university hospital including 22 infants requiring resuscitation at birth who had serial (five time points) neutrophil and monocyte CD11b (marker of cell adhesion), intracellular reactive oxygen intermediates (ROI; cell activation) and Toll-like receptor (TLR; endotoxin recognition) before and after endotoxin stimulation ex vivo compared to neonatal controls. Results : All neonates requiring resuscitation at delivery ( n  = 122 samples) had higher neutrophil and monocyte CD11b and TLR-4 expression compared with adults and neonatal controls. Neonates with abnormal neuroimaging and/or severe NE had increased CD11b, ROI and TLR-4. Increased polymorphonuclear leukocytes TLR-4 expression was associated with increased mortality in infants with NE. Conclusion : Innate immune dysregulation in the first week of life is associated with severity of outcome in neonatal brain injury in this cohort and may be amenable to immunomodulation.